Heritage and allegiance: a history of Njelele sacred place in Matobo hills from the 1960s to the present - Munyukwi, Kudakwashe (Midlands State University, 2017)
This thesis was an investigation into the conflicts at Njelele sacred place. There had been intense conflicts between various stakeholders over the control and management of the shrine from at least the 1960s to the present. This thesis therefore argue that even though there are many causes of conflicts at Njelele like quest for political control over the shrine, attempts by the post –colonial government to politicize the shrine, ethnicisation or tribalisation of the shrine, cultural transformation of the shrine over the past years, scarcity of resources, interdependence of people who wish to achieve different goals the contests over the control of the shrine can largely be attributed to colonialism. Most of the causes can be traced back or had their roots in the colonial period. There were both direct and indirect impacts on the shrine and these impacts fuelled conflicts at the shrine